Reviving and Reclaiming Our Native Food System: Leadership Experiences of a Research Project’s Community Advisory Board - Bowers, Rhonda; Harris, Pat; Harris, Clarisse; Lone Fight, Kathryn; Weed, Ina; White, Nelson (Journal of Agriculture, Food Systems, and Community Development, 2019)
As proud Native community leaders who call the Wind River Reservation home, our battles for sovereignty and respect are not just part of a long-ago history. Claiming our self-empowerment and putting it to good use on behalf of our entire community are challenged more often than we care to recount. In the matter of sustainable food security, those of us who agreed to serve as members of the Growing Resilience Community Advisory Board (CAB) were reminded of such events. Our CAB was established in 2016 as an oversight group for community wellbeing for a University of Wyoming (UW)–initiated and National Institutes of Health (NIH)–funded research project on gardening and health. See the <a title="press release archive" href="http://www.icontact-archive.com/archive?c=488966&f=60033&s=84565&m=984645&t=257c360ddc23fcec50d37942ed548ee4169a6c0d76d51e227fa886af9ecdf0c7" target="_blank" rel="noopener">press release for this article.